Selected Psychological Features of Personality and the Level of Internality in Patients of a Multidisciplinary Hospital - Victoria Kononets; Alua Miraleyeva; Saule Balmagambetova; Gulmira Zharmakhanova; Gulnara Batyrova; Ilya Derkach; Nadiar Mussin (West Kazakhstan Medical Journal)
The levels of extraversion-introversion, neuroticism, psychoticism, and locus of control are of particular interest when researching samples of people with various health disorders. The study aims to describe the psychological profile according to Eysenck’s personality type and internality characteristics in patients of a multidisciplinary hospital’s trauma, neurological, and cardiological departments. The combined survey/case-control study with 58 in-patient participants and 58 controls was performed from July to December 2023 in a multidisciplinary clinic in Aktobe. The Rotter Locus of Control Questionnaire and the Hans and Sibylle Eysenck Personality Type Questionnaire were used to collect data. The levels of extraversion, neuroticism, and psychoticism were significantly higher in neurological patients (17.0 (15.0;18.0), 18.0 (14.0;21.0), and 11.0 (9.0;13.0), respectively). Cardiac patients showed the highest indicators of social desirability, 17.0 (16.0; 18.0), and the internality of achievements, 7.0 (5.5; 8.0). There were no significant differences between the groups in general internality and internality toward failure and health. Weak positive correlations with age were found on the scales of lying and internality in the field of achievements, failures, and family relationships, as well as a negative correlation between age and internality concerning health and illness (0.27; 0.28; 0.24; 0.38; -0.22, respectively). Analyzing the psychological profile of cardiac patients in our study confirmed the researchers’ version of type D behavior (a combination of negative emotionality, restraint, lack of self-confidence, and uncertainty) in this group. Compared with the controls, in-patient participants recorded relatively low levels of internality in business relations and, vice versa, high internality in family relations, particularly in men. Thus, stress caused by illness, especially long-term chronic pathology, affects the patient’s psychological profile and initiates a reassessment of values.